Migraine and frequent tension-type headache are not associated with multiple sclerosis in a Norwegian case-control study. (December 2016) - Gustavsen, MW; Celius, EG; Winsvold, BS; Moen, SM; Nygaard, GO; Berg-Hansen, P; Lie, BA; Zwart, J-A; Harbo, HF
Background: Inconsistent results have been obtained with regard to headache comorbidity in multiple sclerosis (MS). Objective: Investigate the one-year prevalence of migraine and tension-type headache (TTH) in Norwegian MS patients and relate this to clinical parameters. Methods: A questionnaire concerning headache was administered to 756 MS patients and 1090 controls and used to determine the one-year prevalence of migraine and frequent TTH. Results: No significant differences were seen between patients and controls or between patients with different disease course. Less migraine was observed in patients with Expanded Disability Status Scale score (EDSS) ≥4.0. Conclusions: This case-control study does not support an association between migraine or TTH and MS.